Gryporhynchidae (Cestoda: Cyclophyllidea) in Mexico: species list, hosts, distribution and new records - Ortega-Olivares, Mirza P.; García-Prieto, Luis; García-Varela, Martín (Zootaxa, 2014)
As a result of this study, 8 new host (Botaurus lentiginosus for Glossocercus caribaensis and Valipora mutabilis; Egretta caerulea for Valipora minuta; Egretta thula for Glossocercus cyprinodontis; Egretta tricolor and Nycticorax nycticorax for Glossocercus caribaensis; Pelecanus occidentalis and Platalea ajaja for Paradilepis caballeroi) and 31 new locality records for gryporhynchid cestode species in Mexico are presented. With these data, the total number of species of this group of helminths in Mexico becomes 25 (19 named species and 6 unidentified taxa), which have been registered as parasites of fishes (47 host species) and (or) birds (20 host species). This information comes from 102 localities, pertaining to 20 of 32 Mexican states. Five of the 25 taxa have been exclusivelly collected in fishes, 7 in fish-eating birds, and 13 in both groups of hosts. The most frequent metacestodes found in Mexican fishes are the merocercoids of Cyclustera ralli, Valipora mutabilis, Parvitaenia cochlearii and Valipora campylancristrota; in adult stage, Glossocercus caribaensis was the species with the largest host spectrum, while Paradilepis caballeroi has the widest distribution range. The work includes parasite/host lists, as well as habitat, distribution, references and information on specimens’ deposition.